Correlation between Fischer-Tropsch catalytic activity and composition of catalysts - Ali, S. (Biomed Central Limited, 2011)
This paper presents the synthesis and characterization of monometallic and bimetallic cobalt and iron nanoparticles supported on alumina. The catalysts were prepared by a wet impregnation method. Samples were characterized using temperature-programmed reduction (TPR), temperature-programmed oxidation (TPO), CO-chemisorption, transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM-EDX) and N2-adsorption analysis. Fischer-Tropsch synthesis (FTS) was carried out in a fixed-bed microreactor at 543K and 1 atm, with H2/CO = 2 v/v and space velocity, SV = 12L/g.h. The physicochemical properties and the FTS activity of the bimetallic catalysts were analyzed and compared with those of monometallic cobalt and iron catalysts at similar operating conditions. H2-TPR analysis of cobalt catalyst indicated three temperature regions at 506◦C (low), 650◦C (medium) and 731◦C (high). The incorporation of iron up to 30% into cobalt catalysts increased the reduction, CO chemisorption and number of cobalt active sites of the catalyst while an opposite trend was observed for the iron-riched bimetallic catalysts. The CO conversion was 6.3% and 4.6%, over the monometallic cobalt and iron catalysts, respectively. Bimetallic catalysts enhanced the CO conversion. Amongst the catalysts studied, bimetallic catalyst with the composition of 70Co30Fe showed the highest CO conversion (8.1%) while exhibiting the same product selectivity as that of monometallic Co catalyst. Monometallic iron catalyst showed the lowest selectivity for C5+ hydrocarbons (1.6%).